“Seiko musina morari?”: the carnivalesque modes of the pungwe institution in selected Shona novels - Viriri, Advice (Unisa Publications, 2016)
This study is an analysis of the depiction of Pungwe (Night Vigil) in selected Shona novels and songs. The study uses Bakhtin’s description of a historical phenomenon-cum-literary theoretical framework called the carnivalesque. The theory’s tenets apply to the analysis of Shona novels and songs. It is demonstrated that although the depiction of the Pungwe in the literature varies between or among Shona authors, there is general consensus that the carnivalesque elements of the Pungwe encouraged a subversion that undermines virtually all categories of social privilege in the novels and the songs. The carnivalesque theory encourages analysis of fiction and songs that produce the pluralising of meanings of the Pungwe in the Shona novels and songs that are rendered semantically unstable. Narrative instability is transgressive and its liberating potential manifests itself through the different activities and energies mobilised at the Pungwe. As a carnival square, the Pungwe institution found in the Shona novel and songs is portrayed as the main site for resisting imperial domination in Rhodesia. Linked to the carnivalesque is the idea of dialogism. The study reveals that the dialogism experienced at the Pungwe as depicted in the Shona novels and in some popular songs contain multiple voices that combine and manifest diversity of ideological perspectives. Pungwe narratives in the novels and songs are represented as liminal spaces where plurality of political consciousness on the historical causes and trajectories of the liberation struggle in Zimbabwe are revealed. The study contributes to the scholarship on the Shona novel by revealing how Pungwe which is an oral institution finds permanent residence in the narrative interstices of the Shona novel.